Economic sustainability, environmental sustainability and constructability indicators related to concrete- and steel-projects - Zhong, Y.; Wu, Peng (Elsevier Ltd, 2014)
© 2015. Due to an increased awareness of sustainable development and constructability, the construction industry is now facing challenges to reduce energy consumption, carbon emissions and other negative environmental impacts while maintaining high economic sustainability and constructability performance. This study investigates the performance of reinforced concrete framed (RC-framed) and structural steel framed (SS-framed) buildings on economic sustainability, environmental sustainability and constructability performance indicators in Singapore. The results suggest that economic sustainability, environmental sustainability and constructability performance are important in the decision making process for the selection of structural materials. While RC-framed buildings outperform SS-framed buildings in structural costs, maintenance costs and financial costs, SS-framed buildings outperform RC-framed buildings in increased area, flexibility of internal space, recycling rate, recyclability, waste rate, water consumption, labour saving, construction duration and construction quality. Both RC-framed buildings and SS-framed buildings performed on the same level in noise pollution and construction safety. The present study also provides a good guidance of selecting structural materials based on economic, environmental and constructable considerations.